Heterogeneity in euro-area monetary policy transmission: Results from a large multi-country BVAR model - Martin Mandler; Michael Scharnagl; Ute Volz (Deutsche Bundesbank, 2016)
We study cross-country differences in monetary policy transmission across the large four euro-area countries (France, Germany, Italy and Spain) using a large Bayesian vector autoregressive model with endogenous prior selection. Drawing both on the posterior distributions of the cross-country differences in impulse responses as well as on a battery of other tests, we find real output to respond less negatively in Spain to monetary policy tightening than in the other three countries, while the decline in the price level is weaker in Germany. Bond yields rise more strongly and more persistently in France and Germany than in Italy and Spain.
Keywords: C11; C54; E52; 330; monetary policy; transmission mechanism; euro area; Bayesian vector autoregression